Political Preferences of Voters with Disabilities in the 2024 Elections: Values, Perceptions, Trends and Satisfaction Vs Ideological Values and Group Strength - Yayan Sahi; Ramli Mahmud; Udin Hamim (Journal of Law, Politic and Humanities, 2024)
This study aims to analyze the political preferences of voters with disabilities in the 2024 election based on value preferences, perceptions, tendencies, and satisfactions, as well as the influence of ideological values and group strengths. The method used is qualitative with a phenomenological approach. Primary data sources came from the KPU (General Election Commission), Bawaslu (Election Supervisory Agency), and Kesbangpol (National Unity and Political Agency) of Bone Bolango Regency, as well as local voters with disabilities, while secondary data was obtained from analysis of reports, report books on election organizer activities, research journals, and election laws. The data analysis process includes data reduction, data presentation, and drawing conclusions. The results of the analysis revealed that of the 1,450 voters with disabilities registered in 18 sub-districts, only 650 exercised their voting rights, while the other 800 did not participate. This condition indicates the low engagement of voters with disabilities, which is influenced by their orientation to their value preferences, perceptions, tendencies, and satisfactions, which is often distorted by negative labeling in the context of electoral politics. The lack of adequate accommodation for electoral rights and accessibility for voters with disabilities also leads to disappointment, which ultimately reinforces ideological patterns and group identities that make them reluctant to channel their political rights. This study suggests the importance of further development of an ideal political preference strengthening model for voters with disabilities to reduce the instability of their political participation due to disappointment with the conduct of the elections.